THE EFFECT OF POP UP BOOK MEDIA ON VERBAL LINGUISTIC INTELLIGENCE IN CHILDREN AGED 5-6 YEARS AT RA AL-IS SYAH HAKIM MEDAN - Rahimah; Zahriani, Nurul (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2022)
This research was conducted at RA Al-Is Syah Hakim Medan. This type of research is experimental research with a quantitative approach. This research method uses Quasi Experimental Designs with Non Equivalent Control Group Design. The population is 29 children with total sampling technique, so that the entire population is used as a sample. This study aims to determine: (1) linguistic verbal intelligence of children; (2) Linguistic verbal intelligence of children using pop up book media; (3) The significant influence of pop up book media on the linguistic verbal intelligence of children at RA Al-Isyah Hakim Medan. The results of the study show that the use of pop up book media affects the linguistic intelligence of children aged 5-6 years. This is illustrated by the research results which obtained an average pre-test of 26.72 and an average post-test of 52.08. So that the linguistic verbal intelligence of children in the experimental class is better than the control class with an average pre-test of 25 and an average of 44.83 in post-test. Based on the results of the hypothesis testing, tcount > ttable is 3.226> 2.131 with a significant number of α = 0.005 Thus the hypothesis Ho is rejected and Ha is accepted so that it can be stated that there is a significant effect of the use of Pop Up Book Media on Verbal Linguistic Intelligence in Children Aged 5-6 Years at RA Al-Isyah Hakim Medan. Media Pop Up Book, Linguistic Verbal Intelligence.